Kekuatan Hukum Akta Perdamaian Antara Pemegang Polis Dengan Perusahaan Asuransi Yang Dicabut Izin Usahanya - Afrialdo Siagian (Kyadiren, 2020)
The purpose of this study is to analyze the legal strength of the peace deed between the insurer and the insured during revocation of the insurance company's business license and to analyze the implementation of claim payments to the insured party based on the deed. Based on the current study, it can be concluded that the peace deed is acceptable as legal force even though it takes into account the good intentions of the parties. The implementation of the fulfillment of compensation for insurance claims needs to be followed by the dissolution of the legal entity and the appointment of a liquidator team as stipulated in Article 44 of the Insurance Law. The liquidator team needs to correct the good faith of the parties based on the deed. In addition, revisions are made to the provisions for revocation of business licenses accompanied by the dissolution of the insurance company legal entity and the appointment of a liquidation team by the Financial Services Authority (OJK) if it is deemed to endanger the interests of policy holders as regulated in Article 71 paragraph (3) of the Insurance Law.